Analysis of The Influence of Convenience, Trust, and Website Quality Perspectives on Shopee User Loyalty - Ella Mulyantika Aprilia (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to analyze the influence of the perspective of convenience, trust, and website quality on the loyalty of shopee users. Research data were obtained from answers to questionnaires on 110 respondents who were randomly distributed in the cities of Jakarta, Bogor and Malang. The research was conducted using random sampling method with an error rate of 5%. The research was conducted quantitatively using the SPSS version 22 application. The results indicated that: 1) Partial trust has a significant and very strong effect on the loyalty of the shopee application users (2) The convenience and quality of the website does not have a significant effect on the loyalty of the shopee users (3) The variable of trust partially has the strongest influence among other variables on the loyalty of the shopee users (4 ) The simultaneous effect of convenience and trust variables is the strongest compared to the simultaneous effect of the other two simultaneous variables (5) The simultaneous effect of convenience, trust and website quality variables is simultaneously the strongest compared to all other variables.